Ludwig Senfl, Motets for Four Voices (N-V) - Gasch, Stefan (2022)
The second volume of the New Senfl Edition (NSE) provides the second half of the motets for four voices and includes many hitherto unknown works by Senfl (some of them fragments), renowned motets, such as Senfl's Nisi Dominus, or the polyphonic setting of Non moriar sed vivam, which Senfl sent to Martin Luther in 1530 as a consolation. Editions will also render three Salve settings (including a Christological adaption), a multitexted Regina caeli, as well as nearly all of Senfl's humanist motets (Quid vitam sine te, Sum tuus in vita (i), Tristia fata boni) accessible. The Critical Reports accompanying the editions offer information on every motet with regard to the texts set to music, the plainchant models, an evaluation of the sources (incl. a synoptic overview of variant readings), as well as details on the history of each composition.